2020
DOI: 10.1007/s41669-020-00245-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Nivolumab in Patients with Advanced, Previously Treated Squamous and Non-squamous Non-small-cell Lung Cancer in England

Abstract: Objective The aim of this study was to investigate the cost effectiveness of nivolumab versus docetaxel in previously treated, advanced non–small-cell lung cancer (NSCLC) in England and assess how conditional reimbursement within the Cancer Drugs Fund (CDF) can be used to ensure timely patient access to effective treatments. Methods Cost-effectiveness models developed for the National Institute for Health and Care Excellence (NICE) TA483 (squamous) and TA484 (non-squamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…From a Chinese healthcare system perspective, our previous cost-effectiveness analysis revealed that second-line nivolumab was unlikely to be cost-effective compared with docetaxel in patients with advanced NSCLC, despite the subgroup analysis showing the improved cost-effectiveness of nivolumab in the patients with PD-L1TPS ≥1% ( 12 ). Although this finding did not concur with the cost-effectiveness analyses conducted in other countries showing a favorable cost-effectiveness of nivolumab versus docetaxel in previously treated advanced NSCLC patients regardless of PD-L1 expression ( 13 , 14 ), different perspectives, trial source used for analysis, and approach to modeling used between these studies have to be highlighted that may explain the inconsistency. Considering that nivolumab is recommended as the preferred second-line treatment for advanced NSCLC patients without ALK or EGFR mutations regardless of their PD-L1 expression in China, evidence regarding the impact of PD-L1 test results on the comparative cost-effectiveness of second-line nivolumab versus docetaxel from a Chinese health system perspective is urgently needed to inform Chinese healthcare policy making.…”
Section: Introductioncontrasting
confidence: 81%
“…From a Chinese healthcare system perspective, our previous cost-effectiveness analysis revealed that second-line nivolumab was unlikely to be cost-effective compared with docetaxel in patients with advanced NSCLC, despite the subgroup analysis showing the improved cost-effectiveness of nivolumab in the patients with PD-L1TPS ≥1% ( 12 ). Although this finding did not concur with the cost-effectiveness analyses conducted in other countries showing a favorable cost-effectiveness of nivolumab versus docetaxel in previously treated advanced NSCLC patients regardless of PD-L1 expression ( 13 , 14 ), different perspectives, trial source used for analysis, and approach to modeling used between these studies have to be highlighted that may explain the inconsistency. Considering that nivolumab is recommended as the preferred second-line treatment for advanced NSCLC patients without ALK or EGFR mutations regardless of their PD-L1 expression in China, evidence regarding the impact of PD-L1 test results on the comparative cost-effectiveness of second-line nivolumab versus docetaxel from a Chinese health system perspective is urgently needed to inform Chinese healthcare policy making.…”
Section: Introductioncontrasting
confidence: 81%
“…20,31,52 However, for the treatment of advanced melanoma [53][54][55] and metastatic colorectal cancer, 56 nivolumabipilimumab combination therapy was not found to be cost-effective compared with a variety of other treatments, including both immunotherapy and chemotherapy. Several cost-effectiveness studies [57][58][59][60][61][62][63] have investigated nivolumab monotherapy as second-line treatment for patients with advanced NSCLC. Many studies have compared nivolumab monotherapy with docetaxel monotherapy, and most of those studies have found that nivolumab was not cost-effective compared with docetaxel in a variety of health care settings.…”
Section: Nivolumab-ipilimumab Chemotherapymentioning
confidence: 99%
“…Many studies have compared nivolumab monotherapy with docetaxel monotherapy, and most of those studies have found that nivolumab was not cost-effective compared with docetaxel in a variety of health care settings. [57][58][59][60][61][62] In addition, nivolumab was not found to be cost-effective compared with erlotinib 57 and nivolumab was dominated by atezolizumab (ie, less effective and more expensive than atezolizumab). 63 However, the results of 2 other studies have suggested that introducing PD-L1 testing or basing treatment on different PD-L1 expression thresholds may improve the cost-effectiveness of nivolumab.…”
Section: Nivolumab-ipilimumab Chemotherapymentioning
confidence: 99%
“…Several economic studies around the world assessed the ICIs as second-line treatments for NSCLC, and the cost-effectiveness results were inconsistent among different countries. A total of three studies, one each from Switzerland ( Matter-Walstra et al, 2016 ), Australia ( Gao and Li, 2019 ), and England ( Rothwell et al, 2021 ) showed that nivolumab is not cost-effective compared with docetaxel for patients with previously treated advanced NSCLC except in England. One US-based study found that pembrolizumab is cost-effective versus docetaxel for second-line treatment of advanced NSCLC patients with PD-L1 ≥50% ( Huang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%